A randomized, double‐blind, placebo‐controlled crossover study of the effects of levetiracetam on cognition, mood, and balance in healthy older adults. (21st July 2017) - Schoenberg, Mike R.; Rum, Ruba S.; Osborn, Katie E.; Werz, Mary Ann
Summary: Objective: The cognitive and mood effects of levetiracetam (LEV) in older adults are not known. This study compared the cognitive and mood effects of LEV to placebo in healthy older adults. Methods: Cognitive, mood, and balance variables were compared between LEV and placebo using a randomized, double‐blind, placebo‐controlled crossover study with two 5‐week treatment periods. Healthy volunteers (n = 20) aged 65–80 (mean age 72.4) received either LEV or placebo in which the LEV target dose was 1, 000 mg/day. Volunteers, aged 65–80, were without epilepsy to limit potentially confounding the impact of seizures and/or underlying neuropathology on outcomes. LEV was initiated at 250 mg twice a day for 2 weeks, then increased to 500 mg twice a day for 2 weeks, and then tapered to 250 mg twice a day for 1 week. This was randomized with placebo for the two treatment arms. Measures included standardized neuropsychological, mood, and balance tests yielding 32 variables. Balance was assessed using subjective report (e.g., A‐B neurotoxicity scale) and objective data (e.g., Berg Balance Scale). Results: Average LEV serum concentration was 16.9 (standard deviation [SD} 7.7). Repeated‐measures analysis of variance (ANOVA) found no differences between LEV and placebo phases for 29 (90.6%) of 32 variables including no change in balance. Performance on LEV was better than placebo on a visual memory (MCG Complex Figure Recall; p = 0.007) and two attention tests (Trail Making Test, Part A, p = 0.009; Stroop Interference, p = 0.004). There was a trend for greater irritability and fatigue (POMS Anger and Fatigue) during the LEV phase (p = 0.029, p = 0.035). Effect‐size changes were generally small (Cohen d < 0.5). Significance: LEV was well tolerated in this elderly population in terms of cognition, mood, and balance. When anticonvulsant medication is indicated for older adults, LEV has pharmacokinetic advantages, and these data indicate no adverse impact on cognition or balance.